Associations between ADRB1 and CYP2D6 gene polymorphisms and the response to β-blocker therapy in hypertension. (June 2015) - Wu, Dingchang; Li, Ganyang; Deng, Maoqing; Song, Wei; Huang, Xiaohua; Guo, Xiaoru; Wu, Zhengzheng; Wu, Shiyang; Xu, Jiasen
Objective: To investigate the associations between β1 -adrenergic receptor ( ADRB1 ) and cytochrome P450 2D6 ( CYP2D6 ) gene polymorphisms and β-blocker treatment outcomes in patients with hypertension. Methods: Chinese patients with essential hypertension were treated with the β-blocker metoprolol and followed up for 12 weeks. xTAG® liquid-chip technology was used for CYP2D6 100 C > T and ADRB1 1165G > C genotyping. Associations between gene polymorphisms and antihypertensive therapy outcomes were assessed by generalized linear model fitting. A decrease of ≥ 10 mmHg in systolic blood pressure indicated an effective treatment outcome. Results: A total of 93 patients were included in the study. Mutant allele frequencies of 61.29% and 58.60% were obtained for ADRB1 and CYP2D6, respectively. There was no significant interaction between the effects of ADRB1 and CYP2D6 gene polymorphisms on treatment outcome. Patients homozygous for the mutant ADRB1 genotype (CC) had better treatment outcomes than those heterozygous for the mutation (GC). Interestingly, β-blocker treatment duration was an independent factor associated with treatment outcome. Conclusions: The ADRB1 1165G > C gene polymorphism and β-blocker treatment duration are independent factors associated with β-blocker treatment outcome. These findings suggest that the selection of antihypertensive therapy should take into consideration the patient's genotype.